2013
DOI: 10.1016/j.carbpol.2012.10.062
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and swelling behavior of xanthan-based hydrogels

Abstract: In this work xanthan chains were crosslinked by esterification reaction at 165 °C either in the absence or in the presence of citric acid. Higher crosslinking density was obtained using citric acid, as evidenced by its lower swelling degree. Tensiometry, a very precise and sensitive technique, was applied to study swelling rates and diffusion mechanisms of water, which was initially quasi-Fickian, controlled by wicking properties, changing to Fickian or Anomalous, depending on hydrogel composition. Hydrogels s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
132
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(141 citation statements)
references
References 44 publications
3
132
0
6
Order By: Relevance
“…In most published reports on the hydrogel swelling, values of n close to 0.5 or over 0.5 are presented. Only a few papers report values of n<0.5 [25,[43][44][45][46][47].…”
Section: Case III (Or Anomalous Diffusion Non-fickian Diffusion)mentioning
confidence: 99%
“…In most published reports on the hydrogel swelling, values of n close to 0.5 or over 0.5 are presented. Only a few papers report values of n<0.5 [25,[43][44][45][46][47].…”
Section: Case III (Or Anomalous Diffusion Non-fickian Diffusion)mentioning
confidence: 99%
“…Variety of dosage forms like tablets (Boyapally et al, 2010, Kanjanabat & Pongjanyakul, 2011, discs (Yehia et al, 2008;Jaipal et al, 2013), patches (Abu-Huwaij et al, 2011;Kaur & Kaur, 2012;Govindasamy et al, 2013) and gels (Das et al, 2012;Bueno et al, 2013) have been reported in the literature for buccal delivery of drugs. Buccal discs are flat, thin solid unit non-flexible compacts; and are similar to buccal tablets.…”
Section: Introductionmentioning
confidence: 99%
“…When soils have increasing amounts of water, dehydrated biopolymer gels (Figure 6a,b) or biopolymer-clay matrices (Figure 6c,d) will adsorb and transfer water to hydrogels with a resulting volumetric expansion (i.e., swelling) [111,112]. The elastic properties of biopolymer hydrogels, such as their tensile strength and stiffness, diminish exponentially with increased water content [113], resulting in a remarkable reduction in soil strength, to approximately 1/10th of the strength of the dried state in a fully saturated condition.…”
Section: Hydro-dependency and Clogging Effect Of Biopolymersmentioning
confidence: 99%